ANALYSIS OF FACTORS CAUSE REDUCTION SAWAH RICE FARMERS IN CENTRAL DISTRICT TAPANULI - Muhammad Buchari Sibuea (AGRIUM: Jurnal Ilmu Pertanian, 2016)
Poverty rice farmers is an actual problem that is being surrounded people who need to look for solution of the problem and strategies to overcome them. Still encountered problems in implementation, so that the rice farmers in the village Tukka District of Central Tapanuli still poor, can not meet all the basic needs as clothing, food and shelter. This study aims to reveal and analyze the factors causing poverty rice farmers. The results showed that poverty rice farmers in the village Tukka caused by the mental attitude of the farmers themselves, the lack of agricultural inputs and the lack of government incentives system, so the production and quality of the crop continued to decline, which in turn will lead to lower income farmers.Keywords: Farmers paddy, poverty, income